Effect of periampullary diverticulum on technical success and complications of endoscopic retrograde cholangiopancreatography: Single center experience - Mohammed A. Omar (Journal of Digestive Endoscopy, 2015)
Context: The incidence of the periampullary duodenal diverticulum (PAD) varies widely from 1 to 32.8%. Although it is usually asymptomatic, its association with various pathological conditions such as choledocholithiasis increased the incidence of complications and cannulation failures after endoscopic retrograde cholangiopancreatography (ERCP) has been well recognized in various studies. Aim: The aim of this study was to investigate and compare the success rate, difficult cannulation, and complications between patients with and without PAD. Settings and Design: A prospective observational study. Subjects and Methods: The study includes 1022 consecutive patients who underwent an ERCP during the period from June 2010 to June 2015. The patients were divided into 2 groups according to the presence (Group A, 114 patients) or absence (Group B, 908 patients) of PAD. Statistical Analysis Used: SPSS version 16. Results: Successful cannulation was achieved in up to 90.4% and 95.9% in Groups A and B, respectively (P = 0.12). The difficulty at attempting this goal was different between the groups (33.3% vs. 16%, P < 0.001). Duodenal perforation and recurrent biliary stones formation were the only significant post-ERCP complications between both groups. Multivariate logistic regression analysis showed 3 significant variables (abnormal papilla, the presence of diverticula, and stricture) with odds ratios indicating a difficult cannulation attempt. Conclusion: The finding of a PAD should not be considered an obstacle to a successful biliary cannulation, but requires more skills. However, it is associated with difficult cannulation, prolonged cannulation and procedure time, decreased the rate of successful stone removal, and increased the incidence of primary and recurrent biliary stones formation.